2004
DOI: 10.1182/blood-2003-12-4276
|View full text |Cite
|
Sign up to set email alerts
|

Active transport of imatinib into and out of cells: implications for drug resistance

Abstract: Imatinib is a tyrosine kinase inhibitor that is effective in the treatment of chronic myeloid leukemia (CML). Not all patients achieve cytogenetic response. Some patients even lose the initial cytogenetic response. In this study, we investigated the active cellular transport of imatinib to gain a better understanding of the possible mechanisms of imatinib resistance. We used the leukemic cell line CCRF-CEM and its drug-resistant subline VBL 100 to measure the uptake of carbon 14 ( 14 C)-labeled imatinib. Imati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
456
1
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(491 citation statements)
references
References 44 publications
18
456
1
16
Order By: Relevance
“…SLC22A1 (Organic Cationic Transporter 1, OCT1) mediates the uptake of many organic cations from the blood into epithelial cells, and in 2004 Thomas et al 17 reported that SLC22A1 was a critical transporters of Imatinib. Subsequently, multiple studies have been conducted addressing the interaction between SLC22A1 and Imatinib and consequently, a number of mutations have been found to be involved in the pharmacokinetics and pharmadynamics of many chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC22A1 (Organic Cationic Transporter 1, OCT1) mediates the uptake of many organic cations from the blood into epithelial cells, and in 2004 Thomas et al 17 reported that SLC22A1 was a critical transporters of Imatinib. Subsequently, multiple studies have been conducted addressing the interaction between SLC22A1 and Imatinib and consequently, a number of mutations have been found to be involved in the pharmacokinetics and pharmadynamics of many chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Increasing body of evidence recognized that influx-and efflux-transporters of ABC (adenosine triphosphatebinding cassette) 12,13 and SLC (solute carrier) families with great affinity to Imatinib influence clinical responses. [14][15][16][17][18] Patients with low expression or activity of OCT1 (encoded by SLC22A1) had a lower probability of achieving a cytogenetic or molecular remission to CML. Improved progression free survival and overall survival was also observed in patients with higher OCT1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular uptake and retention (IUR) of imatinib in tumor cells is believed to be a critical factor for response, as it is considered to determine the effective imatinib concentration at the therapeutic targets within the tumor cell (Thomas et al, 2004;White et al, 2006;Wang et al, 2008). The IUR of imatinib relies on the delicate balance between drug uptake and efflux.…”
Section: Introductionmentioning
confidence: 99%
“…The putative clinical significance of potential imatinib uptake transporters has extensively been investigated in the last decade as reflected by the numerous (pre-) clinical studies that have been conducted to investigate their role in the pharmacokinetics and/or pharmacodynamics of imatinib (Thomas et al, 2004;Crossman et al, 2005;White et al, 2006White et al, , 2007White et al, , 2010Hu et al, 2008;Wang et al, 2008;White and Hughes, 2012;Nies et al, 2014). SLC22A1, also referred to as organic cation transporter (OCT) 1, has frequently been implicated in the intracellular uptake and disposition of imatinib in CML cells (Thomas et al, 2004;White et al, 2006), although controversy exists with regard to its precise role (Burger et al, 2013;Nies et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Inversely to the drug efflux pump proteins, the human organic cation transporter 1 (OCT1) mediates the active transport of Imatinib into cells, and inhibition of OCT1 decreases the intracellular concentration of Imatinib [115]. OCT1 was also found to be expressed in significantly higher levels in patients who achieved a CCR to Imatinib than in those who were more than 65% Ph chromosome positive after 10 months of treatment [116].…”
Section: Drug Intakementioning
confidence: 99%